Relacionando reestruturação produtiva e comprometimento: o caso de um banco em Fortaleza (CE) - Silva, Paulo Williams Rocha da (2011)
The productive restructuring has established a new way of promoting changes in organizational structures and processes in order to allow companies to keep pace with the in creased levels of competition. If, in one hand, the changes introduced through innovations brought productivity gains, on the other, they changed the working relationships, generating positive and negative impacts, regarding the commitment of employees. According to Nogueira et al. (1999), the new scenario has stimulated organizations to deploy not only technological changes, but rather new forms of work organization, aimed at more flexible and integrated businesses, in order to raise productivity to cope with the market environment, whose fundamental characteristics were unpredictability and complexity. In these circumstances the companies began a productive restructuring process. Considering this reality, the aim of this study is to investigate the impact of productive restructuring in organizational commitment (affective, normative and instrumental) of the employees of Alfa Bank in Fortaleza- CE. This is a quantitative research, conducted through a survey with five subsidiaries of the study in the city of Fortaleza, out of a total of 50 respondents. In the collection of field data we used two instruments, of which, the first was the scale of organizational commitment, created by Mowday, Steersand Porter (1979), and a second questionnaire developed by the author himself, with the focus on the occurrence of technological and organizational innovations and their impact on commitment. In the treatment of field data, we used Excel and SPSS. Methods of analysis were employed for combining descriptive analysis, correlation and mean comparison tests. The significance level adopted was 95% overall. In some respects, however, given the relevance to this work and the requirement represented by the 95% significance, results were also analyzed with a rate of 90%. Among the most significant results, it was found out that there is a high level of general involvement of the employees in the Target Company; that the high level of commitment is related to the profile of respondent employees and that the impacts of productive restructuring either in the field of organizational or technological innovations, cause a low impact on the commitment of people, denying, to a certain extent, the hypotheses of this research.